Women at risk: Catalysts of gender violence (2020)
The characteristics of gender-based violence are common at different levels, both at the macro social level and at home micro-violence. The fight against this epidemic and all prevention tasks require revealing a set of prejudices and complicities that foster attacks against women. Assuming our responsibility towards violence against women will allow us to build more harmonious and inclusive coexistence within the great diversity that, in terms of gender, presents postmodern life. This book focuses on a set of concepts, usually considered isolated, that form a plot of facilitation, typified as Catalysts of violence against women. They are a set of operations and processes whose participation is essential for the spread of the different epidemics of violence against women that plague humanity. This book proposes to try to disarm and hinder the action of these social accelerators, which can promote greater effectiveness of the various prevention programs. This shows how each of these catalysts has a powerful and long tradition in facilitating violence against women. This research attempts to provide instruments for analysis and resolution of gender violence, enabling interventions that are more precise and effective than those we have at the moment. Harm prevention and assistance for women at risk are a priority, not only in LatinAmerican societies but also throughout the world.